1997
DOI: 10.1105/tpc.9.8.1411
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Post-Transcriptionally Suppressed Transgene Expression That Confers Resistance to Tobacco Etch Virus Infection in Tobacco.

Abstract: Tobacco lines expressing transgenes that encode tobacco etch virus (TEV) coat protein (CP) mRNA with or without nonsense codons give rise to TEV-resistant tissues that have reduced levels of TEV CP mRNA while maintaining high levels of transgene transcriptional activity. Two phenotypes for virus resistance in the lines containing the transgene have been described: immune (no virus infection) and recovery (initial systemic symptoms followed by gradual recovery over several weeks). Here, we show that at early ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(29 citation statements)
references
References 40 publications
2
27
0
Order By: Relevance
“…These are the ' immunity ' or ' resistant ' phenotype (R ; no symptoms and no accumulation of virus) and the ' recovery ' phenotype (RC ; systemic symptoms that gradually disappear in newly developed leaves some time after inoculation). Recently Tanzer et al (1997) have shown that R lines inoculated at earlier developmental stages are indeed susceptible to virus infection followed by quick recovery from symptoms, suggesting that both R and RC phenotypes are reversible by meiosis and are manifestations of the same process. Slight differences in the developmental stage could explain our results with line P1-51, which showed mostly asymptomatic, virus-free plants but also had some viruscontaining plants with different degrees of quick recovery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These are the ' immunity ' or ' resistant ' phenotype (R ; no symptoms and no accumulation of virus) and the ' recovery ' phenotype (RC ; systemic symptoms that gradually disappear in newly developed leaves some time after inoculation). Recently Tanzer et al (1997) have shown that R lines inoculated at earlier developmental stages are indeed susceptible to virus infection followed by quick recovery from symptoms, suggesting that both R and RC phenotypes are reversible by meiosis and are manifestations of the same process. Slight differences in the developmental stage could explain our results with line P1-51, which showed mostly asymptomatic, virus-free plants but also had some viruscontaining plants with different degrees of quick recovery.…”
Section: Discussionmentioning
confidence: 99%
“…When a plant is transformed with a viral sequence, PTGS will suppress accumulation of the transgene mRNA and of any viral RNA with sequence similarity with the transgene, leading to protection (English et al, 1996). PTGS probably occurs by cytoplasmic degradation of the targeted RNAs (Lindbo et al, 1993 ;Sijen et al, 1996 ;Tanzer et al, 1997) and a similar phenomenon has been described recently in nontransgenic, virus-infected plants (Ratcliff et al, 1997).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…A similar degradation smear below the full-length transcript on a northern has been reported for transgenic N. benthamiana plants in which the LUCIFERASE gene had been silenced (Kjemtrup et al, 1998). In addition, the occurrence of truncated, polyadenylated, and nonpolyadenylated RNAs corresponding to 5# and 3# regions of posttranscriptionally silenced genes has been previously described (Smith et al, 1990;Goodwin et al, 1996;Lee et al, 1997;Metzlaff et al, 1997;Tanzer et al, 1997;Han and Grierson, 2002), suggesting that transgene degradation is gene specific.…”
Section: Discussionmentioning
confidence: 66%
“…Among the possibilities he mentioned are the control of vira1 infections, the generation of hybrid vigor, and the tissue-specific regulation of gene families. A number of recent publications (Que et al, 1997;Ratcliff et al, 1997;Tanzer et al, 1997; have provided further insights into both the mechanisms and functions of gene silencing in plants, including the tantalizing suggestion that signals triggering cosuppression can move .…”
Section: Post-transcriptional Regulation: It's Not Only Proteinsmentioning
confidence: 99%